Respuesta :
-x+y=2
y=2+x
5/3*x-2y=-2
5/3*x- 2 (2+x)= -2
5/3*x-4-2x=-2
5/3x -2x=4-2
x(5/3-2)=2
x(5/3-6/3)=6/3
x*(-1/3)=6/3
-x=6
x=-6
y=x+2
y=-6+2
y=-4
y=2+x
5/3*x-2y=-2
5/3*x- 2 (2+x)= -2
5/3*x-4-2x=-2
5/3x -2x=4-2
x(5/3-2)=2
x(5/3-6/3)=6/3
x*(-1/3)=6/3
-x=6
x=-6
y=x+2
y=-6+2
y=-4
Answer:
The solution of the given system of equation is (-6,-4)
Step-by-step explanation:
Given system of equations [tex]\frac{5}{3}x-2y=-2 \\\\-x+y=2[/tex]
We have to solve the given system of equation
Consider the given system
[tex]\frac{5}{3}x-2y=-2 [/tex] .........(1)
[tex]-x+y=2[/tex] .......(2)
We first simplify the equation (1) , we have
Multiply whole equation by 3,
[tex]5x-6y=-6 [/tex] ...........(3)
Multiply equation (2) by 5 , we have
[tex]-5x+5y=10[/tex] ..........(4)
Now add equation (3) and (4) , we have
[tex]5x-6y+(-5x+5y)=-6+10 [/tex]
[tex]5x-6y-5x+5y=4[/tex]
[tex]-y=4[/tex]
[tex]y=-4[/tex]
Substitute y = - 4 in (2) , we get
[tex]-x+(-4)=2[/tex]
[tex]\Rightarrow -x=2+4=6[/tex]
[tex]\Rightarrow x=-6[/tex]
Thus, x = -6 and y = -4
The solution of the given system of equation is (-6,-4)